Farmers' adaptation to climate variability assessment of effectiveness and barriers based on local experience in Southern Philippines - Pulhin, Florencia B. (Journal of Environmental Science and Management, 2016)
This study assessed the effectiveness of and barriers to adaptation of upland farming househols in Bukidnon Province, Southern Philippines to climate variability. Using focus group discussions, key informant interviews and household surveys combined with the analysis of climate variability in the area, the study described key adaptation strategies commonly practiced at the household and community levels in relation to crop production and income generation, domestic and farm water supply, soil conservation, health and livelihood; and assessed the effectiveness and barriers in the implementation of these strategies. There were few variations in adaptation strategies were noted, current strategies were perceived to be generally effective although some barriers exist in their implementation. Among these barriers include high cost, limited adaptaton options, and difficulty in implementation. Despite the perceived effectiveness, future uncertainty is a major concern since climate variability is likely to worsen, threatening health, food and livelihood security. Planned adaptation founded on robust current and future vulnerability assessments is necessary to address the future risks associated with the changing climate. Moreover, to realize effective farmers' adaptation to future climate change impacts, the anticipated critical adaptation barriers should be successfully overcome.